Cellulose aerogels prepared from an aqueous zinc chloride salt hydrate melt. (10th February 2016) - Schestakow, Maria; Karadagli, Ilknur; Ratke, Lorenz
Abstract : Highlights: Cellulose aerogels were prepared from an aqueous zinc chloride salt hydrate melt. A considerable effect of the regenerative fluid on the resulting structure and properties is discussed. Outstanding mechanical properties for highly porous materials are observed. Abstract: Monolithic cellulose aerogels are prepared using a salt hydrate melt based on cheap zinc chloride tetrahydrate (ZnCl2 ·4H2 O) that can be washed out of the wet gel-body by using common solvents such as water, ethanol, isopropanol or acetone. Cellulose aerogels with concentrations of 1–5 wt.% cellulose were produced. These aerogels are characterized with respect to shrinkage, density and surface area as well as mechanical properties and micro-structure via SEM. Cellulose aerogels regenerated in acetone show a specific surface area of around 340 m 2 g −1 being 60% higher than those regenerated in water. The onset of irreversible plastic deformation under compressive load is around 0.8 MPa for acetone-regenerated aerogels and thus a factor of two larger compared to ethanol regenerated ones. The Young's modulus depends almost linearly on the cellulose concentration which is observed for all regenerative fluids with the exception of water. The results achieved are presented in light of the polarity and ability of solvation of ZnCl2 ·4H2 O in the regenerative fluids used.